Comparative study of photosynthetic capacity in lower leaves in the canopy of dwarf and semidwarf wheat - H.W. LI; J. ZHANG; Q. ZHENG; B. LI; Z.S. LI (Photosynthetica, 2022)
Semidwarf wheat contributes to significant yield increase worldwide, however, few dwarf cultivars of wheat are cultivated due to grain yield penalty. In this study, a new dwarf wheat Triticum aestivum L., cv. Xiaoyan 101, was investigated to explore its photosynthetic performance and yield potential. In the comparison of the semidwarf wheat cultivars, Jing 411 and Xiaoyan 101, although the first three leaves (including flag leaves) did not differ significantly in both genotypes, Xiaoyan 101 conferred a higher content of photosynthetic pigments and higher photochemical efficiency but had lower contents of hydrogen peroxide and malondialdehyde in lower leaves in the canopy. In addition, the antioxidant enzymes-encoding genes were upregulated while the senescence-associated genes (TaSAG3, TaSAG5, TaSAG7, and TaSAG12) were downregulated in lower leaves in the canopy of Xiaoyan 101. Ultimately, Xiaoyan 101 produced approximate or even higher grain yield than the local semidwarf wheat varieties. Therefore, it is possible to breed dwarf wheat with enhanced photosynthetic activity but without yield sacrifice.